Inhibition of OCT4 binding at the MYCN locus induces neuroblastoma cell death accompanied by downregulation of transcripts with high-open reading frame dominance - Nakatani, Kazuma; Kogashi, Hiroyuki; Miyamoto, Takanori; Setoguchi, Taiki; Sakuma, Tetsushi; Kugou, Kazuto; Hasegawa, Yoshinori; Yamamoto, Takashi; Hippo, Yoshitaka; Suenaga, Yusuke (Frontiers in Oncology, 2024)
Amplification of MYCN is observed in high-risk neuroblastomas (NBs) and is associated with a poor prognosis. MYCN expression is directly regulated by multiple transcription factors, including OCT4, MYCN, CTCF, and p53 in NB. Our previous study showed that inhibition of p53 binding at the MYCN locus induces NB cell death. However, it remains unclear whether inhibition of alternative transcription factor induces NB cell death. In this study, we revealed that the inhibition of OCT4 binding at the MYCN locus, a critical site for the human-specific OCT4–MYCN positive feedback loop, induces caspase-2-mediated cell death in MYCN-amplified NB. We used the CRISPR/deactivated Cas9 (dCas9) technology to specifically inhibit transcription factors from binding to the MYCN locus in the MYCN-amplified NB cell lines CHP134 and IMR32. In both cell lines, the inhibition of OCT4 binding at the MYCN locus reduced MYCN expression, thereby suppressing MYCN-target genes. After inhibition of OCT4 binding, differentially downregulated transcripts were associated with high-open reading frame (ORF) dominance score, which is associated with the translation efficiency of transcripts. These transcripts were enriched in splicing factors, including MYCN-target genes such as HNRNPA1 and PTBP1. Furthermore, transcripts with a high-ORF dominance score were significantly associated with genes whose high expression is associated with a poor prognosis in NB. Because the ORF dominance score correlates with the translation efficiency of transcripts, our findings suggest that MYCN maintains the expression of transcripts with high translation efficiency, contributing to a poor prognosis in NB. In conclusion, the inhibition of OCT4 binding at the MYCN locus resulted in reduced MYCN activity, which in turn led to the downregulation of high-ORF dominance transcripts and subsequently induced caspase-2-mediated cell death in MYCN-amplified NB cells. Therefore, disruption of the OCT4 binding at the MYCN locus may serve as an effective therapeutic strategy for MYCN-amplified NB.